La classe virtuelle synchrone à l'université, un levier de transformation de la professionnalité enseignante? - Verquin Savarieau, Béatrice; Daguet, Hervé (Médiations et médiatisations, 2020)
Do synchronous online classrooms modify teacher professionality, and what are the resulting transformations? This research conducted with teachers at Forse digital campus at the University of Rouen illustrates that media-based communication devices make possible new ways of intervening for evening classes and teleworking. It is thus the professional teaching act that is questioned in its institutional, epistemic dimensions and the foundation of the expression of professional teaching action such as the absence of the instituting body of the teacher.
Keywords: classe virtuelle synchrone; dispositif de communication médiatisée; formation à distance; intégration technologique; multimodalité; professionnalité enseignante